FAKTOR-FAKTOR RISIKO SINDROM METABOLIK TERHADAP HIPERTENSI PADA REMAJA AKHIR - Cantika Risna Andini (2023)
Background: The prevalence of metabolic syndrome has increased in recent decades in the world population, especially in the United States and Asia, due to the rapid westernization of lifestyles. B. Dietary habits that lead to reduced physical activity and increasingly sophisticated technological and robotic developments may be some of the risk factors for metabolic syndrome. The aim of this study was to determine whether there is a relationship between late adolescent metabolic syndrome and risk factors for hypertension. Methods: This research was conducted using an analytic observational research design with a cross-sectional approach. Respondents in this study included medical students at UPN "Veteran" Jakarta who were in the late adolescence category. The data taken in this study used primary data using questionnaires and physical examinations. Results: bivariate test results obtained the relationship between gender with hypertension (p=0.001), central obesity with hypertension (p=0.022), nutritional status with hypertension (p=0.018), and between food intake with hypertension (p=0.002). Male respondents had a 8 times greater risk of hypertension and food intake had a 8 times risk of hypertension. Conclusion: There are significant associations between gender, central obesity, nutritional status, and food intake in hypertension. Male students can pay more attention to their lifestyle to avoid hypertension. All students can pay more attention to food intake to avoid hypertension